Influence of Contemporary Educational Qualification on Self-Efficacy: A Study of Madrasa Students (Al-Qamar, 2023)
This research is an endeavor to investigate the influence of contemporary educational qualification on self-efficacy among madrasa students. The nature of the research was quantitative. A survey design was applied to gather the data from participants. The population of the study were the students of madrasas in Punjab. 300 madrasa students of darja ʻAma level were selected out of 10 madrasas as a sample of the study. As an instrument, a questionnaire measuring the self-efficacy of students was used which contains 28 items. To ensure the reliability, a pilot study of the questionnaire with 70 madrasa students was conducted. The value of Cronbach’s α was 0.81. The data were analyzed using SPSS 26 in which descriptive and inferential statistics were incorporated. One way ANOVA test was applied for comparison. To further analyze the results of one-way ANOVA, post hoc test was run. Two-way ANOVA was also run to examine the main and interaction effects. Key findings of the research indicated a statistically significant difference in the self-efficacy of madrasa students in different groups with regard to contemporary educational qualification. The findings revealed that, the madrasa students with greater level of contemporary education demonstrated greater levels of self-efficacy in comparison to those with lower level of contemporary educational qualification. However, no significant difference was seen in comparison of graduation level madrasa students with the intermediate level madrassa students. The results of two way ANOVA suggested that there is an impact of contemporary educational qualification and madrassa types and has an interaction between interaction between contemporary educational qualification and madrassa types on self-efficacy.Based on findings, the researcher suggests that the contemporary subjects such as vocational, professional, technological and international languages should be included in the madrasa curriculum. Moreover, training and counselling workshops should be administered to assist madrasa students for overall development including their intellectual, social, emotion well-beings.
Keywords: Self-Efficacy; Madrassa students; Contemporary Education